Role of CyPA in cardiac hypertrophy and remodeling. Issue 12 (23rd December 2019) - Cao, Mengfei; Yuan, Wei; Peng, Meiling; Mao, Ziqi; Zhao, Qianru; Sun, Xia; Yan, Jinchuan
Abstract: Pathological cardiac hypertrophy is a complex process and eventually develops into heart failure, in which the heart responds to various intrinsic or external stress, involving increased interstitial fibrosis, cell death and cardiac dysfunction. Studies have shown that oxidative stress is an important mechanism for this maladaptation. Cyclophilin A (CyPA) is a member of the cyclophilin (CyPs) family. Many cells secrete CyPA to the outside of the cells in response to oxidative stress. CyPA from blood vessels and the heart itself participate in a variety of signaling pathways to regulate the production of reactive oxygen species (ROS) and mediate inflammation, promote cardiomyocyte hypertrophy and proliferation of cardiac fibroblasts, stimulate endothelial injury and vascular smooth muscle hyperplasia, and promote the dissolution of extracellular matrix (ECM) by activating matrix metalloproteinases (MMPs). The events triggered by CyPA cause a decline of diastolic and systolic function and finally lead to the occurrence of heart failure. This article aims to introduce the role and mechanism of CyPA in cardiac hypertrophy and remodeling, and highlights its potential role as a disease biomarker and therapeutic target.